Русская литературная собака (Материалы к биографическому словарю) [The Russian Literary Dog: Materials for a Biographical Dictionary] - Sobolev, Alexander (Slavica Revalensia, 2023)
This unconventional dictionary, having over 100 entries, is the first attempt ever to list dogs that belonged to Russian turn-of-the-century and 20th-century writers (for example, Alexander Blok, Anton Chekhov, Vladimir Mayakovsky, Maximilian Voloshin, etc.).